(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2024)
This article explores key prospects for Islamic finance, including ethical principles, financial stability, economic development, globalization and innovation. He highlights such problems as complexity, standardization problems, limited product innovation, liquidity management and the regulatory framework. Despite these challenges, Islamic finance continues to grow globally as an Islamic alternative to traditional finance with the potential to promote inclusive economic growth and financial stability.